Virulent Leptospira interrogans Induce Cytotoxic Effects in Human Platelets in vitro Through Direct Interactions - Vieira, Monica Larucci; Nascimento, Ana Lucia T. O. (Frontiers in Microbiology, 2020)
Leptospirosis is a prevalent zoonotic disease, caused by bacteria of the genus Leptospira. Leptospirosis frequently leads to hemostatic disturbances, and the severe cases are marked by hemorrhages and low platelet number in circulation, which is associated with the patients’ poor outcomes. Nevertheless, Leptospira-platelet interactions remain poorly explored. In this study, we performed a series of in vitro experiments evaluating whether leptospires induce human platelet aggregation, activation, and morphological changes. Platelets were incubated with virulent L. interrogans and the platelet outcomes were assessed by aggregometry, flow cytometry, and scanning and transmission electron microscopy. Our results show that leptospires alone do not induce platelet aggregation and activation, and induce platelet cytotoxic effects instead, by clearly inducing platelet disruption and detachment. We show for the first time that virulent leptospires do interact directly with platelets, an event that could trigger pathophysiological effects during the infection. This study might serve as a basis for the development of novel treatments for the disease.